Enhancing the health of NHS staff: eTHOS — protocol for a randomised controlled pilot trial of an employee health screening clinic for NHS staff to reduce absenteeism and presenteeism, compared with usual care - Rachel Adams; Rachel Jordan; Peymané Adab; Tim Barrett; Sheriden Bevan; Lucy Cooper; Ingrid DuRand; Pollyanna Hardy; Nicola Heneghan; Kate Jolly; Sue Jowett; Tom Marshall; et al. (Pilot and Feasibility Studies, 2022)
Abstract Background Staff absenteeism and presenteeism incur high costs to the NHS and are associated with adverse health outcomes. The main causes are musculoskeletal complaints and mental ill-health, which are potentially modifiable, and cardiovascular risk factors are also common. We will test the feasibility of an RCT to evaluate the clinical and cost-effectiveness of an employee health screening clinic on reducing sickness absenteeism and presenteeism. Methods This is an individually randomised controlled pilot trial aiming to recruit 480 participants. All previously unscreened employees from four hospitals within three UK NHS hospital Trusts will be eligible. Those randomised to the intervention arm will be invited to attend an employee health screening clinic consisting of a screening assessment for musculoskeletal (STarT MSK and STarT Back), mental (PHQ-9 and GAD-7) and cardiovascular (NHS Health Check if aged ≥ 40, lifestyle check if < 40 years) health. Screen positives will be given advice and/or referral to recommended services. Those randomised to the control arm will receive usual care. Participants will complete a questionnaire at baseline and 26 weeks; anonymised absenteeism and staff demographics will also be collected from personnel records. The co-primary outcomes are as follows: recruitment, referrals and uptake of recommended services in the intervention arm. Secondary outcomes include the following: results of screening assessments, uptake of individual referrals, reported changes in health behaviours, acceptability and feasibility of intervention, indication of contamination and costs. Outcomes related to the definitive trial include self-reported and employee records of absenteeism with reasons. Process evaluation to inform a future trial includes interviews with participants, intervention delivery staff and service providers receiving referrals. Analyses will include presentation of descriptive statistics, framework analysis for qualitative data and costs and consequences presented for health economics. Discussion The study will provide data to inform the design of a definitive RCT which aims to find an effective and cost-effective method of reducing absenteeism and presenteeism amongst NHS staff. The feasibility study will test trial procedures, and process outcomes, including the success of strategies for including underserved groups, and provide information and data to help inform the design and sample size for a definitive trial. Trial registration ISRCTN reference number 10237475 .